Daily Utility and Satisfaction With Rollators Among Persons With Chronic Obstructive Pulmonary Disease - Hill, Kylie; Goldstein, R.; Gartner, E.; Brooks, D. (W.B. Saunders Co., 2008)
Hill K, Goldstein R, Gartner EJ, Brooks D. Daily utility and satisfaction with rollators among persons with chronic obstructive pulmonary disease. Objective: To characterize the daily utility and satisfaction with rollators in patients with chronic obstructive pulmonary disease (COPD). Design: Cross-sectional observational study. Setting: Community. Participants: COPD patients describing dyspnea during activities of living, who had been provided with a rollator by a health care professional within the preceding 5-year period. Interventions: Not applicable. Main Outcome Measures: Three questionnaires were administered in random order. The St. George's Respiratory Questionnaire was used to measure health-related quality of life, version 2.0 of the Quebec User Evaluation of Satisfaction with Assistive Technology was used to assess satisfaction with the rollator, and a structured questionnaire was used to obtain information regarding daily utility of the device and barriers to its use. Demographic data were obtained through patient interview. Anthropometric data, measurements of resting lung function, and 6-minute walk distance were extracted from the medical records. Results: Twenty-seven (10 men) patients (forced expiratory volume in 1 second, 35.1%±22.3% predicted) completed the study. Sixteen (59%) patients reported daily rollator use. All patients used the rollator to assist with ambulation outdoors, but 16 (59%) patients stated that they did not use the rollator for any activity in their home. Although satisfaction with the rollator was high, women were less satisfied with the weight of the device than men (P=.008). Thirteen (48%) patients reported being embarrassed while using the device. Conclusions: COPD patients provided with a rollator for use during daily life were most satisfied with its effectiveness and least satisfied with its weight. Daily use was generally high with over half the patients using the rollator on a daily basis. Rollators were more often used outdoors than indoors. © 2008 American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation.